Csornai Premontrei Apátság (2024)
Keywords: csorna

„Tekintsd e művet, Isten”. A zsámbéki premontrei templom és kolostor története - Valter, Ilona (Martin Opitz Kiadó, 2023)
Keywords: zsámbék

Premontrei monostor maradványait találhatták meg a Háros-sziget mentén - Pulszky Társaság – Magyar Múzeumi Egyesület (Magyar Múzeumok, 2022)
Keywords: csút

Egy IV. Béla által alapított monostor maradványait találhatták meg a régészek a Háros-szigetnél (PestBuda, 2022)
Keywords: csút

A kaposfői premontrei prépostság feltárása Bárdudvarnok határában - Aradi, Csilla M.; Molnár, István (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: kaposfő

Adatok a hatvani, premontrei, prépostság történe téből - Demény-Dittel, Lajos (Hatvani Kalendárium, 2022)
Keywords: hatvan

A zsámbéki premontrei templom középkori falfestményeiről egy 1895. évi restaurátori árajánlat alapján - Fehér, Ildikó (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

A zsámbéki premontrei templom 13. századi boltozatai - Fehér, Krisztina (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

A somlóvásárhelyi premontrei apácák - Jakits, Orsolya Johanna (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: somlóvásárhely

A jászói Keresztelő Szent János-monostor középkori története - Kotrusová, Júlia (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: jasov

A premontrei rend Árpád-kori építkezései kutatásának vázlata Pons Johannis (Jánoshida) példáján - Mezey, Alice (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: jánoshida

Az Árpád-kori kökényesi premontrei prépostság épületmaradványai barokk falakban - Mezey, Alice (Hatvani Kalendárium, 2022)
Keywords: nagykökényes

Árpád-házi Szent Erzsébet tisztelete a premontrei rendben lánya, Boldog Gertrúd tevékenysége kapcsán, különös tekintettel a középkori Magyarországra - Nagy, Györgyi (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: 🇭🇺 hungary (general)

A premontrei rend türjei temploma - Nagy, Veronika; Horogszegi, Tamás; Gaylhoffer-Kovács, Gábor (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: türje

Az ócsai premontrei templom építéstörténete és díszítési rétegeei - Raffay, Endre (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: ócsa

Félúton az apátságok és a koldulórendek között: A premontreiek anyagi viszonyai a középkori Magyarországon - Romhányi, Beatrix F. (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: 🇭🇺 hungary (general)

Rendi építészeti hagyományok és a premontreiek Árpád-kori kolostorai - Szakács, Béla Zsolt (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: 🇭🇺 hungary (general)

Késő gótikus boltozat az egykori zsámbéki premontrei prépostság épületében - Szőke, Balázs (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

A zsámbéki prépostság története a hitelesítő ásatás tükrében - Valter, Ilona (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

Szemelvények a bozóki, a bényi, a sági és a turóci monostorok történetéből - Žažová, Henrieta (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: bzovík; bíňa; klaštor pod znievom; šahy

Megjegyzések a bozóki prépostság birtokösszeíró okleveléhez - Bagi, Dániel (Prépostok, apátok, vikáriusok: Tanulmányok, 2021)
Remarks on the census deed of the Bošice provost
Num Pages: 312 Pp.
Keywords: bzovík

A gyulafirátóti premontrei prépostság alapítása és monostorának viszontagságai – kiegészítések és kérdések - Horogszegi, Tamás (Veszprémi Szemle Várostörténeti folyóirat, 2021)
Keywords: gyulafirátót

Az ELTE Egyetemi Könyvtár és Levéltár Cod. Lat. 119 kódexének kottás premontrei fedéltöredékei - Gilányi, Gabriella (“Mestereknek gyengyének”: Ünnepi kötet Madas Edit hetvenedik születésnapjára, 2020)
[Premonstratensian cover fragments in the Cod. Lat. 119, University Library and Archives of the Eötvös Loránd University]
Num Pages: 684 Pp.
Keywords: 🇭🇺 hungary (general)

Egy prépostállítás buktatói. A Drugetek és a Sztriteiek konfliktusa a leleszi konvent körül - Szőcs, Tibor (Aetas: Történettudományi folyóirat, 2020)
The pitfalls of a provost nomination. The conflict between the Drugs and the Strites around the Lleesz convent
Keywords: leles

Hroznata a úřad probošta v Teplé - Trnka, Pavel (Minulostí Západočeského kraje, 2019)
[Hroznata and office of provost of Teplá]
Keywords: teplá; 👤 hroznata of bohemia

Kísérlet a bárdudvarnok-szentbenedeki premontrei prépostság környezeti rekonstrukciójára - Aradi, Csilla M.; Molnár, István (Genius loci – Laszlovszky 60, 2018)
[An attempt to reconstruct the environment of the Premonstratensian abbey of Bárdudvarnok-Szentbenedek]
Num Pages: 407 Pp.
Keywords: kaposfő

Az ócsai premontrei prépostság régészeti kutatása - Csoltkó, Emese (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The village of Ócsa is situated to the south of Budapest in Pest County. The first mention of the existence of the Premonstratensian provostry is dated to 1234 in the so-called Catalogue of Ninive, which mentions that Ócsa is the filial of the convent of Jászó ( Jasov, Slovakia). The church with three naves and two towers at its western facade was built in the first half of the 13th century. During the construction works there were some modifications in the original plans, as the church was planned with another vaulting section towards at the west, but that was, along with the vaulting of the naves, never finished. Minor reconstruction works can be dated to the Middle Ages; for example wall-paintings and the Gothic pastoforium. The Premonstratensians left Ócsa before the Ottoman occupation period, but as a parish church, it didn’t lose the function which is attested by the 15th century demolition of the rood-screen. The church was used by the Calvinist congregation since 1560. As part of the preparation for the reconstruction works, there was archaeological research between 1986 and 1992 which was led by Juan Cabello. This included a systematic, full-scale excavation in the church and in the churchyard. In the course of the excavation, the monastery building with the one side and three pit houses from the 12th–13th century was found. The surrounding and inside of the church were used as a cemetery. The first reconstruction work was realized in the second half of the 18th century ( József Teleki’s works between 1774 and 1777). In the 18th century the church was damaged by natural disasters like lightning and fire. Thus another renovation was necessary, led by Ottó Tandor (1897–1900). In 1909 Ottó Sztehlo renewed the damaged northern portal. The elevation of the towers of the church was carried out by Ernő Foerk in 1923. Finally, the recent renovation of the church was conducted by Tibor Gál between 1989 and 1995.
Keywords: ócsa

Szent Euszták és vértanú társai prépostság | Háros-sziget, Budapest XXII. - Galuska, Tünde (A pálos rend építészeti emlékei, 2018)
Keywords: csút

Adalékok a jászói Keresztelo Szent János premontrei monostor középkori történelméhez - Kotrusová, Júlia (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The Monastery of St. John the Baptist in Jasov belongs among the oldest Premonstratensian monasteries in modern Slovakia. The circumstances surrounding the arrival of Premonstratensians in Jasov and the year of foundation of the monastery are amongst the most debated problems in the history of the Jasov provostship. The source of these controversies is the fact that the foundation charter was not preserved. The opinions of historians on the foundation of the monastery vary. A number of historians assume that it was founded at the turn of the 12th and 13th centuries, possibly at the beginning of the 13th century. I argue that a charter issued by King Béla IV in 1255 can contribute to clarification of the foundation of the convent. The document re-establishes the originalprivileges of the monastery. The earliest references to Premonstratensian monasteries in Hungary is preserved in the Ninive catalogue, specifically in its second registry. The properties of the monastery also raise a number of questions. The institution owned properties of high value in the Middle Ages. The oldest mention of their estate possession dates back to the above mentioned charter issued by King Béla IV in 1255. The lands mentioned in the charter were compact. Besides the original property described by the charter, in 1255 lands were provided for the monastery that Béla acquired from Duke Coloman. During the medieval and early modern period Jasov was a central property of the Jasov provostship. Due to its location and its vicinity to the monastery, it became more and more prominent in the 13th century, when it gained urban privileges, most importantly market rights.
Keywords: jasov

Gyulafirátót, avagy a rendi építészeti hagyományok átjárhatósága - Szakács, Béla Zsolt (Genius Loci. Laszlovszky 60, 2018)
(Gyulafirátót or the permeability of the monastic architectural traditions)
Keywords: gyulafirátót

A levéltárak titkos élete. A Csornai Premontrei Apátság levéltárainak évszázadai - Vajk, Ádám (Soproni Szemle: Helytörténeti folyóirat, 2018)
[The secret life of archives. Centuries of the archives of the Premonstratensian abbey of Csorna]
Keywords: csorna

Lelesz patrónusai - Kovács, Viktória (Történelmi Szemle, 2017)
The Patrons of Lelesz. Based on a number of hitherto unused sources, the present paper outlines the history of patronage over the Premonstratensian priory of Lelesz from its foundation until the end of the Middle Ages. It seeks to answer the question of what foundations the authority of the archbishop of Esztergom was based on, and when was it effectively extended over this church in the diocese of Eger, which was founded by another prelate, and had been mostly subjected to private patronage until the middle of the 14th century. The annex contains the publication of the judicial decision which, in 1355, annulled the claim to the patronage over Lelesz of the Eszenyi and Sztritei branches of the Baksa kin, who had thus far regarded the monastery as a kind of „family church”.
Keywords: leles

A bárdudvarnoki premontrei prépostság területén 2015-ben végzett régészeti feltárás - Aradi, Csilla M.; Molnár, István (Archaeologia - Altum Castrum Online, 2016)
Keywords: kaposfő

Premontrei prépostság feltárása Bárdudvarnokon - Aradi, Csilla M.; Molnár, István (Fiatal Középkoros Régészek VI. Konferenciájának Tanulmánykötete, 2015)
Keywords: kaposfő

A leleszi premontreiek szalókai birtoklásának háttere - Kovács, Viktória (Történelmi Szemle, 2015)
[The Background to the Landowning of the Premonstratensians of Lelesz at Szalóka] Although the founding charter of the Holy Cross provostry at Lelesz (today Leles, Slovakia) from 1214, of dubious authenticity, has not survived in the original, one of its later transcriptions from 1334 lists among the grants made by bishop Boleslo of Vác in favor of the provostry a possession called Zolunta. The people of Zolunta are reported to have robbed Russian tradesmen, an act later proved by the tradesmen through ordeal in the church of Buda, whereupon Zolunta was adjudicated to them by court ispán (comes curialis) Egyed. The village was eventually bought by the bishop of Vác from the tradesmen for 82 marks. The possession in question has traditionally been identified in the research with Szalonta in the medieval county of Borsod (Hejőszalonta, Hungary). According to Ambrus Pleidell, however, the provostry owned Szalóka (Solovka, Ukraine), which was variously regarded as belonging to the counties of Bereg and Ung in the Middle Ages. In the course of various lawsuits in 1336, 1343 and 1378, the monastery proved its title to Szalóka in Bereg with the founding charter and its later transcriptions. It is likewise Szalóka that is recorded as a possession of the provostry by the tax register of 1550. In order to establish which possession was in fact owned by the monastery of Lelesz, the author examines the charters which have preserved the relevant part of the founding charter, as well as the medieval variants of the names of the two settlements and their history. Two among the three textual traditions of the founding charter (1214/1334/1342/1364/1406, 1214/1334, 1214/1362) contain variants of the toponym Szalonta, which thus probably figured in the charter of 1214 as well. In the summary transcriptions connected to the presentation of titles in lawsuits (1336, 1343, 1378) it is Szalóka which appears without exception. The forms of toponyms, while fairly similar to each other, certainly refer to different settlements. As for Szalonta, prior to 1319 it was owned by the Ákos kindred, and thereafter by Dózsa Debreceni, voevode of Transylvania – consequently, it surely did not belong to the monastery of Lelesz in the early 14th century. Szalóka, on the other hand, was owned in the first half of the 13th century by Artolf of the Aba kindred, from whom it was purchased by the son-in-law of ban Bánk called Simon. In 1270 it was in the possession of Mihály son of Endre of the Rosd kindred, and in 1285 in that of his widow and new husband, Jakab Lónyai. In a protest made before the chapter of Eger in 1302 the provost of Lelesz claimed that Szalóka belonged to his monastery. On the basis of this information, the most probable solution seems to be that, while the provostry had originally come into the possession of Szalonta by virtue of the founding charter, later in the Angevin period it used the document to prove its title to landowning at Szalóka. During the lawsuits, the monastery probably argued that the Zolunta/Zolounta figuring in the charters in fact referred to Szalóka in Bereg.
Keywords: leles

Premontrei prépostságok a középkori Magyarországon, különös tekintettel a Kaposfői Szent Benedek prépostságra - Aradi, Csilla M. (A Kaposvári Rippl-Rónai Múzeum Közleményei, 2014)
Keywords: kaposfő; 🇭🇺 hungary (general)

Premontrei monostor feltárása Bárdudvarnokon - Aradi, Csilla M.; Molnár, István (Archaeologia - Altum Castrum Online, 2014)
Keywords: kaposfő

Az ócsai református (egykor premontrei) templom építéstörténetének vázlata - Csoltkó, Emese (A múltnak kútja: Fiatal középkoros régészek V. konferenciájának tanulmánykötete, 2014)
[Sketches to the Building History of the Calvinist (Former Premonstratensian) Church of Ócsa]
Keywords: ócsa

Premontrei breviárium és collectionale – Premonstratensian Breviary and Book of Collects - Knapp, Eva (Kép és kereszténység = Image and Christianity, 2014)
Keywords: 📚 premonstratensian (general)

A türjei premontrei prépostság templomának falkép-restaurátori kutatása - József, Lángi (Ko kövön: David Ferenc 73. születésnapjára, 2013)
[Die Erforschung der Wandmalereien und Fassungen in der Kirche der Prämonstratenser-Propstei zu Türje]
Keywords: türje

A magyar királyok genealógiai ciklusa a leleszi premontrei kolostorkápolna középkori falképein - Jékely, Zsombor (Művészettörténeti Értesítő, 2012)
The Premonstratensian monastery of Lelesz, dedicated to the Holy Cross, was founded by Boleszló, the bishop of Vác (1188–1212). Patronage, however, was given over to the king, and later rulers in turn handed patronage of the monastery to their subjects. In 1214, the act of foundation was reinforced and the church of Lelesz consecrated. With the king's support, Lelesz became one of the wealthiest monasteries and an important place of authentication (locus credibilis). The new church of the monastery was built around the middle of the 14th century; in 1362 magister Johannes from Buda was contracted to build the tower. The chapel of Saint Michael, standing to the north of the church, and originally probably also serving as the chapter house, was built under the prior Dominicus of the Pálóci family (1378–1403). Around 1400, this new chapel was fully decorated with wall paintings. Much of the decoration – for example the frescoes of the vault – were destroyed when the chapel was re-vaulted in the 18th century. Still, a complete cycle of wall-paintings survives on the side walls of the chapel. On the south wall, there is a large, three-level image of the Last Judgment, with Christ in the mandorla dominating the scene, accompanied by the apostles on either side. In the lunettes of the north wall, two scenes can be detected: the one to the east depicts Saint Elisabeth of Hungary, while the other is possibly an image of Pope Urban V, in the company of cardinals. On the eastern walls of the chapel, apostles or prophets are depicted, framed by painted tracery. The focus of the paper is the series of figures depicted on the two lower zones of the north wall. As can be determined with the help of fragmentary inscriptions, these figures represent the kings of Hungary, starting from King Saint Stephen. The inscription gives the names of rulers and the number of years they ruled. The cycle is fragmentary, so we do not know exactly how many kings were depicted, but there is enough space for all the Hungarian sovereigns up until the then-current ruler, Sigismund (1387–1437). Such a cycle is unique from the territory of the medieval Kingdom of Hungary. Best parallel is provided by the cycle of initials in the Illuminated Chronicle (c. 1360, Széchényi National Library, Cod. Lat. 404), which also depict the pagan rulers of Hungarian prehistory, giving a complete genealogical cycle. Models of this cycle – just like that of the contemporary Luxemburg genealogy once on the walls of Karlstein castle in Bohemia – were provided by French manuscripts, especially the Grandes Chroniques de France. Emphasis in the cycle is not on individual kings, but on the unity and continuity of the line of Hungarian kings. One figure stands out: the first (badly damaged) ruler of the cycle is depicted enthroned. It is here proposed that the cycle starts with an image of the current ruler, King Sigismund. The style and iconography of the cycle make it a prime example of the International Gothic style, and these characteristic can be explained by the close connections of Lelesz abbey to the royal court.
Keywords: leles

Zsámbéki premontrei prépostsági templom - Szakács, Béla Zsolt (Magyar muvelodéstörténeti lexikon: középkor és kora újkor, 2012)
Keywords: zsámbék

Tihanyi bencés apátsági templom; Türjei premontrei prépostsági templom - Szakács, Béla Zsolt (Magyar muvelodéstörténeti lexikon: középkor és kora újkor, 2011)
Keywords: türje

Premontrei prépostságok az esztergomi érsek joghatósága alatt. A királyi egyházak jogállásának kérdéséhez - Kiss, Gergely (Középkortörténeti tanulmányok, 6: A VI. Medievisztikai PhD-konferencia (Szeged, 2009. június 4-5.) előadásai, 2010)
Premonstratensian provosts under the authority of the archbishop of Esztergom. The question of the royal churches' legal status
Num Pages: 338 Pp.
Keywords: 🇭🇺 hungary (general)

A csornai premontrei monostor a 13-14. században - Vajk, Ádám (Soproni Szemle: Helytörténeti folyóirat, 2010)
The Premonstratensian abbey of Csorna in the 13th-14th centuries
Keywords: csorna

A csornai premontrei prépostság épületének megújulása - Winkler, Gábor (Soproni Szemle: Helytörténeti folyóirat, 2010)
The reconstruction of the Premonstratensian abbey of Csorna
Keywords: csorna

A két apostolfejedelem fejereklyéjének ábrázolása Leleszen: adalékok egy ritka ikonográfia magyarországi előfordulásához - Farbakyné Deklava, Lilla (Műemlékvédelem: Műemlékvédelmi és épitészettörténeti szemle, 2009)
The portrayal of the head relic of two apostle princes in Leles: additions to the incidence of this rare iconography in Hungary
Keywords: leles

Zsámbék elfeledett falképei: Giovanni Battista Cavalcaselle tanítványának felmérése a premontrei templom falképeiről 1895-ből - Fehér, Ildikó (Művészettörténeti Értesítő, 2008)
The forgotten frescoes of Zsámbék. The assessment of the frescoes of the Premonstratensian church by a pupil of Giovanni Battista Cavalcaselle in 1895
Keywords: zsámbék

A Hont-Pázmány nemzetség premontrei monostorai - Tóth, Sándor (BT-Press Könyv- és Lapkiadó, 2008)
Keywords: 🇭🇺 hungary (general); 🇸🇰 slovakia (general)

Premontrei rendházak az Árpád-kori Zalában - Cselenkó, Borbála (Szerzetesrendek az Árpád-kori Zala megyében, 2006)
Premonstratensian abbeys in Zala county in the Árpád era
Num Pages: 130 Pp.
Keywords: 🇭🇺 hungary (general)

A megkerült Pozsonyi Kódex és Szegedi Antifonale, valamint két elkallódott kézirat - Lázs, Sándor. (Magyar Könyvszemle, 2006)
Keywords: szeged

A csornai premontrei monostor alapítása - Vajk, Ádám (Soproni Szemle: Helytörténeti folyóirat, 2004)
The foundations of the Premonstratensian monastery at Csorna
Keywords: csorna

A hatvani premontrei prépostság története 1351-ig - Tóvay Nagy, Péter (Sic Itur ad Astra: Fiatal történészek folyóirata, 2003)
The history of the Premonstratensian priory of Hatvan before 1351
Keywords: hatvan

Eltűnek Hitt Egykori Premontrei Prépostság az Erdélyi Mezőségen - Gábor, Horváth (Magyar Egyháztörténeti Vázlatok Regnum, 2002)
A One-time Premonstratensian Provostry in the Mezőség ofTransylvania That Was Believed to Have Disappeared
Keywords: sic; 📚 premonstratensian (general)

A magyarországi premontrei cirkária az 1241/1242-I tatárjárást követő évtizedekben (az Írásos források alapján) - Körmendi, Tamás (Kút, 2002)
[The Hungarian Premonstratensian province in the years following the Mongol raid of 1241/1242 (according to written sources)
Keywords: 🇭🇺 hungary (general); 🇷🇴 romania (general)

A premontrei rend megtelepedése az Árpád-kori Magyarországon: a rend korai hazai története a kezdetektől az 1235-i Catalogus Ninivensisig II - Körmendi, Tamás (Turul, 2002)
Keywords: 🇭🇺 hungary (general)

Premontreiek - Kovács, Imre Endre; Legeza, Laslo (Mikes Kiadó, 2002)
Keywords: 🇭🇺 hungary (general)

A kancelláriai aprómunkától a gátlástalan birtokosig - Borsa, Iván (Tanulmányok a középkorról: Analecta Medievalia I. (A Pázmány Péter Katolikus Egyetem Bölcsészettudományi Kar Medievisztika Tanszékének kiadványsorozata)., 2001)
From chancellery trifles to ruthless land-owning.
Num Pages: 281 Pp.
Keywords: leles

A 13. századi premontrei monostorjegyzékek magyar vonatkozásairól - Körmendi, Tamás (Történelmi Szemle, 2001)
Hungarian Aspects of the Thirteenth-century Catalogues of Monasteries of the Premonstratensian Order
Keywords: 🇭🇺 hungary (general)

A premontrei rend megtelepedése az Árpád-kori Magyarországon: a rend korai hazai története a kezdetektöl az 1235-i Catalogus Ninivensisig I - Körmendi, Tamás (Turul, 2001)
Keywords: 🇭🇺 hungary (general)

Hiteleshely és a királyi jelenlét I. adatok a leleszi konvent hiteleshelyi működéséhez a 15. század elején - Tóth, Norbert C. (Századok: A Magyar Történelmi Társulat folyóirata, 2001)
Places of authentication and the court of special royal presence. Remarks on the activity of the convent of Leles in the early fifteenth century
Keywords: leles

A hatvani premontrei szerzetes közösség, mint hiteles hely (egy nagyobb tanulmány részlete) - Demény-Dittel, Lajos (Hatvani Kalendárium, 2000)
Keywords: hatvan

Árpás-Mórichida: Szent Jakab apostol plébániatemplom - Lászay, Judit; Galavics, Géza (TKM Egyesület, 2000)
Keywords: mórichida